Optical absorption of BaF[2] crystals with different prehistory when irradiated by high-energy electrons; IOP Conference Series: Materials Science and Engineering; Vol. 110 : Radiation-Thermal Effects and Processes in Inorganic Materials (RTEP2015) - Chinkov E. P. Evgeny Petrovich; Stepanov S. A. Sergey Aleksandrovich; Shtanko (Shtan'ko) V. F. Viktor Fedorovich; Ivanova T. S. (2016, 2016)
Title screen